A reagent to access methyl sulfones - Yaroslav Poplavskyi; Vasyl Ripenko; Sergei Bova; Angelina Biitseva; Yurii V. Dmitriv; Andrei A. Tolmachev; Iryna V. Sadkova; Iryna Pishel; Oleksii Grygorov; Vo Quang Huy Phan; H. V. Rasika Dias; Pavel K. Mykhailiuk (Nature Communications)
Abstract A chemical reagent to access methyl sulfones has been developed. Its reaction with various bis-nucleophiles leads to the rapid formation of previously unknown heteroaromatic methyl sulfones. Analogous strategy can also be used to construct alkyl-, CHF2-, CF3- and even bicyclo[1.1.1]pentane-containing derivatives. These compounds have been demonstrated to have a high potential for use in medicinal chemistry and coordination chemistry.